Peran Pemerintah Desa Dalam Mengembangkan Potensi Anak Muda Desa Ogobayas Kecamatan Mepanga Kabupaten Parigi Moutong - Hariyadi, Hariyadi; Munir, Nurasia; Hasriani, Hasriani (Jurusan Pengembangan Masyarakat Islam Fakultas Dakwah dan Komunikasi Islam, UIN Datokarama Palu., 2025)
This study aims to analyze the strategic role of the village government in Ogobayas in empowering youth through local values-based programs in religion and sports. A descriptive qualitative approach was employed, utilizing participatory observation, in-depth interviews, and document analysis. Informants were selected purposively, and data were analyzed using the interactive model of Miles and Huberman, with triangulation and member checking to ensure validity. The findings reveal that the village government effectively fosters active youth participation through inclusive forums, revitalizes local religious values as a foundation for character development, and promotes sports as a medium of social cohesion and collective identity. Supportive policies and responsive infrastructure further enhance the effectiveness of youth empowerment programs. The study reinforces theoretical frameworks of citizen participation, social theology, and social capital, while offering practical implications for inclusive and sustainable rural development policies, especially in peripheral areas with limited infrastructure but high youth potential.